2007
DOI: 10.1530/rep-06-0227
|View full text |Cite
|
Sign up to set email alerts
|

Direct stimulatory effect of ghrelin on pituitary release of LH through a nitric oxide-dependent mechanism that is modulated by estrogen

Abstract: Ghrelin, a gut peptide with key actions on food intake and GH secretion, has been recently recognized as potential regulator of reproductive function. Thus, in adult female rats, ghrelin has been proven to modulate GnRH/LH secretion, with predominant inhibitory effects in vivo. We analyze herein potential direct pituitary effects of ghrelin on basal and GnRH-stimulated gonadotropin secretion in prepubertal female rats, and its interplay with ovarian inputs, nitric oxide (NO), and hypothalamic differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 69 publications
0
24
0
2
Order By: Relevance
“…26 Gonadal expression of acylated-ghrelin receptors was also shown in Sertoli and Leydig cells of the testis and in follicular, luteal, surface epithelial and interstitial hilus cells of the ovary. 26 Vulliemoz et al 24 showed that ghrelin can inhibit GnRH pulse activity in ovariectomized adult monkey, while Lebrethon et al 9 reported that ghrelin reduces GnRH in the pre-pubertal period in male rats and has no effect in mature rats.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…26 Gonadal expression of acylated-ghrelin receptors was also shown in Sertoli and Leydig cells of the testis and in follicular, luteal, surface epithelial and interstitial hilus cells of the ovary. 26 Vulliemoz et al 24 showed that ghrelin can inhibit GnRH pulse activity in ovariectomized adult monkey, while Lebrethon et al 9 reported that ghrelin reduces GnRH in the pre-pubertal period in male rats and has no effect in mature rats.…”
Section: Discussionmentioning
confidence: 97%
“…26 Gonadal expression of acylated-ghrelin receptors was also shown in Sertoli and Leydig cells of the testis and in follicular, luteal, surface epithelial and interstitial hilus cells of the ovary. 26 Vulliemoz et al 24 showed that ghrelin can inhibit GnRH pulse activity in ovariectomized adult monkey, while Lebrethon et al 9 reported that ghrelin reduces GnRH in the pre-pubertal period in male rats and has no effect in mature rats. Fernandez-Fernandez et al, 27,32 who have investigated the role of ghrelin on sexual maturation, showed that ghrelin inhibits LH The reduced levels of reproductive hormones in β-thalassemic patients could be the result of intercellular iron overload and/or disturbance of the immune system.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies suggest that ghrelin has a central (hypothalamic) inhibitory effect on gonadotropin secretion: luteinizing hormone (LH) pulsatility is suppressed by central administration of ghrelin to rats, monkeys and sheep [28], and ex vivo gonadotropin-releasing hormone (GnRH) secretion by hypothalamic explants from female rats is also inhibited by ghrelin treatment [29]. On the other hand, although ghrelin inhibits the GnRH-induced LH release by pituitary explants, it also has the opposite effect of directly stimulating both LH and follicle-stimulating hormone secretion in vitro [30]. Another level of complexity is added by the differential effects of hormones when given in a fixed or pulsatile manner.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin was largely described to play an essential role in reproduction since db/db mice, which are deleted for leptin gene receptor, and ob/ob mice, which are deleted for leptin gene, are infertile (6,18). Moreover, upregulation of ghrelin induced a decrease in LH surge (26,53), even if the mechanisms involved are yet unknown. Chronic exposition to corticosterone inhibited LH secretion and estrous cycle and ovulation in female rodents (9,10).…”
Section: E252 Chronic Food Restriction and Physical Activitymentioning
confidence: 99%